Iran : The Chronicles of the Subsidy Reform - Guillaume, Dominique; Reza Farzin, Mohammad; Zytek, Roman (Washington, D.C. : International Monetary Fund, 2011)
On December 18, 2010, Iran increased domestic energy and agricultural prices by up to 20 times, making it the first major oil-exporting country to reduce substantially implicit energy subsidies. This paper reviews the economic and technical issues involved in the planning and early implementation of the reform, including the transfers to households and the public relations campaign that were critical to the success of the reform. It also looks at the reform from a chronological standpoint, in particular in the final phases of the preparation. The paper concludes by an overview of the main challenges for the second phase of the reform.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet